A granular formulation of Nomuraea rileyi Farlow (Samson) for the control of Spodoptera frugiperda (Lepidoptera: Noctuidae) - Domenico Pavone (Interciencia, 2009)
A granular formulation of the entomopathogenic fungus Nomuraea rileyi (Farlow) Samson was evaluated against Spodoptera frugiperda (Lepidoptera: Noctuidae). The formulation consisted of 1mm particles of defatted corn germ (DCG) containing 107 conidia/g. This preparation protected the conidia against UV radiation and killed 80% of S. frugiperda larvae in laboratory bioassays. It was shown that the fungus used DCG as a substrate for growth and sporulation, creating foci for further infection. This strategy has great potential for the formulation of fungal biocontrol agents, especially those with a high growth rate.